Answer:
(x - 1)(x + 1)(x² + 1)
Step-by-step explanation:
Step 1: Factor Difference of Squares
(x² - 1)(x² + 1)
Step 2: Factor Difference of Squares for non-complex binomial root
(x - 1)(x + 1)(x² + 1)
And we have our answer!
4x=20-8y
x=5-2y now use this value of x in the second equation...
3(5-2y)+6y=15
15-6y+6y=15
15=15 This is true for any y or x value.
So there are infinitely many solutions as the two equations describe the same line.
Answer:
f(-1) = -4
Step-by-step explanation:
f(-1) simply means that what is f(x) when x = -1?
Just plug in -1 for <em>x</em> to find your answer:
f(-1) = -3(-1) + 2(-1) - 5
f(-1) = 3 - 2 - 5
f(-1) = 1 - 5
f(-1) = -4
Im sorry Im not that good at geometry.